Penegakan Hukum Terhadap Illegal Fishing dan Overfishing Sumberdaya Perikanan : (Dalam Aspek Pertahanan Negara) (International Forum of Researchers and Lecturers, 2023)
This study aims to examine how law enforcement against illegal fishing and overfishing in the Indonesian ocean region is carried out by